Recurrent anencephalic stillbirths: A rare case presentation - Razai, Mohammad S (International Journal of Health Sciences, 2018)
Anencephaly is one of the three major lethal fetal anomalies. Termination of pregnancy is offered for all prenatally diagnosed cases, but some parents choose to continue with pregnancy with full obstetric intervention. I describe the case of a woman who had two pregnancies with anencephalic stillbirths in the third trimester. There is a paucity of well-defined standards of care and management for pregnancies that are carried to the third trimester with this malformation. This case raises important practical questions: Management strategies of recurrent pregnancies with anencephaly, best supportive care during, and after birth and counseling the expectant parents.